Proceedings of the 1st Workshop on Automatic Text Adaptation (ATA) 2018
DOI: 10.18653/v1/w18-7005
|View full text |Cite
|
Sign up to set email alerts
|

Reference-less Quality Estimation of Text Simplification Systems

Abstract: The evaluation of text simplification (TS) systems remains an open challenge. As the task has common points with machine translation (MT), TS is often evaluated using MT metrics such as BLEU. However, such metrics require high quality reference data, which is rarely available for TS. TS has the advantage over MT of being a monolingual task, which allows for direct comparisons to be made between the simplified text and its original version. In this paper, we compare multiple approaches to reference-less quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(113 citation statements)
references
References 24 publications
0
108
0
5
Order By: Relevance
“…QE leverages both the source sentence and the output simplification to provide additional information on specific behaviours of simplification systems which are not reflected in metrics such as SARI. EASSE uses QE features from Martin et al (2018)'s open-source repository 5 . The QE features currently available are: the compression ratio of the simplification with respect to its source sentence, its Levenshtein similarity, the average number of sentence splits performed by the system, the proportion of exact matches (i.e.…”
Section: Word-level Analysis and Qe Featuresmentioning
confidence: 99%
“…QE leverages both the source sentence and the output simplification to provide additional information on specific behaviours of simplification systems which are not reflected in metrics such as SARI. EASSE uses QE features from Martin et al (2018)'s open-source repository 5 . The QE features currently available are: the compression ratio of the simplification with respect to its source sentence, its Levenshtein similarity, the average number of sentence splits performed by the system, the proportion of exact matches (i.e.…”
Section: Word-level Analysis and Qe Featuresmentioning
confidence: 99%
“…Our goal instead, is to analyze the behavior of the MT system when confronted with ungrammatical input. Reference-less evaluation has also been proposed for text simplification (Martin et al, 2018) and GEC (Napoles et al, 2016), while the grammaticality of MT systems' outputs has been evaluated with target-side contrastive pairs (Sennrich, 2017).…”
Section: Notation and Experimental Settingsmentioning
confidence: 99%
“…Research on Quality Estimation has shown promising results on using reference-less metrics to evaluate generated outputs, allowing the automatic assessment to speed-up and scale. This line of work has started to be applied for simplification (Štajner et al 2016;Martin et al 2018), and we believe it needs to be explored further. In addition, human-based evaluation has been limited to three criteria: grammaticality, meaning preservation, and simplicity.…”
Section: Discussionmentioning
confidence: 99%